The influence of other persons and different situations on counterfactual thinking - Ostheimer, Vanessa Geraldine (2013)
The present dissertation deals with the impact of social influence and specific content domains or situations on counterfactual thinking. Counterfactual thoughts are thoughts that describe an alternative past and help people to learn for the future. This thesis provides two new aspects for counterfactual research. The research so far has only looked at selfdetermined situations but not at situations that are influenced by others. However, family and friends influence people’s daily behavior. Five experiments show that people generate counterfactuals not only in situations where they are free to choose what to do, but also in situations where other people influence their behavior. Former research also disagreed upon which variables (especially commission and omission) of a situation lead to more counterfactuals than others. This thesis gives new input for this dispute, as specific content domains are responsible for varying findings. In different situations people inherit a different norm for their behavior. For example, in health situations the norm is a commission, e.g., that people act to protect their health. A deviation from a norm leads to counterfactual thinking, e.g. the person did not act to protect her health. The present thesis integrates the new findings into a new model of counterfactual thinking that explains different content domains and the influence of other persons on one’s behavior. These aspects have a crucial impact on the generation of counterfactuals.